RELEVANSI PENDIDIKAN PESANTREN DENGAN PENDIDIKAN MODERN - Wahyudin Wahyudin (Postgraduate State Islamic Institute (IAIN) Metro, 2014)
The Islamic boarding school is the oldest forms of Islamic educational institution in Indonesia. It’s expected to conform with the most recent developments. If not, the Islamic educational institution will be increasingly left behind by the development of contemporary education. The combination of Islamic education and modern education must be applied, it will make the Islamic educational institution be better. This paper is intended to convey the relevance of Islamic education, in this case boarding school and modern education. The Islamic boarding school should be able to adapt to the current development of education, either through the methods and technologies used. This conclusion is that the Islamic education in school has parallels with general education. In fact, Islamic education today can’t be sight as an anti-modernization and education seem ancient. Therefore, not least the current Islamic education that has been able to transform itself into a parallel education with other education in Indonesia. Although it must be admitted, there is the boarding school that still maintain the pattern of classical education, but by no means anti-renewal. Even today, many boarding schools that already have a higher education institutions, such as : high schools, institutes and universities. This shows, that Islamic education is ready and able to adjust with the times.